Immunomodulatory and anti-inflammatory effects of Aerva lanata in ovalbumin induced allergic asthmatic mice. (10th May 2022) - Sharif, Mariam; Anjum, Irfan; Shabbir, Arham; Mushtaq, Muhammad Naveed
Abstract: Ethnopharmacological relevance: Aerva lanata Linn. ( A. lanata ) is traditionally used for cough, sore throat and asthma. Aim of study: The aim of the present study was to investigate the immunomodulatory and anti-inflammatory potentials of A. lanata in allergic asthmatic mice. Materials and methods: BALB/c mice were administered with three different (methanol, n-hexane and ethyl acetate) extracts of A. lanata two weeks after immunization with ovalbumin and continued for 7 days. Inflammatory cells count was estimated in blood and broncho-alveolar lavage fluid (BALF). RT-PCR was used to find out mRNA expression levels of inflammatory mediators. GC-MS analysis was also carried out. Results: Among three extracts of A. lanata, ethyl acetate extract ameliorated ( p  < 0.001) count of inflammatory cells both blood and BALF remarkably. This study indicated that ethyl acetate extract of A. lanata lowered ( p  < 0.001) the level of inflammatory modulator TNF-α and IgE antibodies. A. lanata reduced ( p  < 0.001) interleukin 4, 5, 13 and enhanced ( p  < 0.001) expression levels of AQP1 and AQP5 in asthmatic mice. GC-MS analysis of ethyl acetate fraction indicated the presence of various anti-oxidant phyto-constituents. The groups treated with A. lanata improved inflammatory, goblet cells hyperplasia scoring and alveolar thickening. Conclusions: The anti-asthmatic effect of A. lanata might be contributed by the suppression of edema, pro-inflammatory cytokines and IgE antibodies, and elevation of aquaporin expression levels, suggesting future study and clinical trials to propose it as a candidate to treat allergic asthma. The anti-oxidant phytochemicals present in A. lanata might be responsible for such potential. Graphical abstract: Image 1